Lactobacillus reuteri Alleviates Gastrointestinal Toxicity of Rituximab by Regulating the Proinflammatory T Cells in vivo - Zhao, Binyan; Zhou, Bailing; Dong, Chunyan; Zhang, Rui; Xie, Daoyuan; Tian, Yaomei; Yang, Li (Frontiers in Microbiology, 2021)
Rituximab (RTX) is a widely used anticancer drug with gastrointestinal side effects, such as nausea, vomiting and diarrhoea. The reason for these side effects is still poorly understood. Previous studies have reported that the intestinal microbiota is associated with the occurrence of disease and the therapeutic effect of drugs. In this study, we observed mucosal damage, inflammatory cell infiltration and increased intestinal inflammatory factor expression in RTX-treated mice. RTX also changed the diversity of the intestinal microbiota in mice, and decreased abundance of Lactobacillus reuteri was observed in RTX-treated mice. Further experiments revealed that intragastric administration of Lactobacillus reuteri in RTX-treated mice attenuated the intestinal inflammatory response induced by RTX and regulated the proportion of helper T (Th) cells. In conclusion, our data characterize the effect of the intestinal microbiota on RTX-induced intestinal inflammation, suggesting that modifying the gut microbiota may represent a positive strategy for managing adverse reactions.